The role of physique, strength and endurance in the achievements of elite climbers. - Mariusz Ozimek; Robert Rokowski; Paweł Draga; Vladimir Ljakh; Tadeusz Ambroży; Marcin Krawczyk; Tomasz Ręgwelski; Arkadiusz Stanula; Karol Görner; Adam Jurczak; Dariusz Mucha (PLoS ONE)
Purpose The primary aim of this study is to determine the principal somatic and motor determinants for elite climbers. Methods Twenty climbers were examined [age: 28.5±6.1 years].The runners were divided into two groups based on their climbing level, according to the International Rock Climbing Research Association (IRCRA). Elite climbers represented a 8b-8c Rotpunkt (RP) climbing level (n = 6), and advanced climbers represented an 7c+-8a RP level (n = 14). The following measurements were assessed: height, weight, lean body mass, upper limb length, arm span, and forearm, arm, thigh and calf circumference. The BMI, Rohrer ratio, and Ape Index were also measured. The following motor tests were assessed: a specific test for finger strength, an arm strength test, and a test of muscle endurance (hanging from 2.5 and 4 cm ledges). In addition, pull ups were used to measure muscle resistance to fatigue. Results Elite climbers recorded significantly higher values for finger strength than advanced climbers (129.08 vs. 111.54 kg; t(18) = 2.35, p = 0.03) and arm endurance (33.17 vs. 25.75 pull ups; t(18) = 2.54, p = 0.02). In addition, the calf circumference was significantly lower in elite climbers than that in advanced climbers (34.75 vs. 36.93 cm; t(18) = 3.50, p = 0.003). Conclusion The results suggest that elite climbers have greater finger strength and arm endurance than advanced climbers.